Hidden complexities of the Frankish Castle : social aspects of space in the configurational architecture of Frankish castles in the Holy Land, 1099-1291 - Mol, Eva (Archaeological studies Leiden University, 2012)
This volume of ASLU presents an approach to Frankish castles with the space syntax, a method and theory that aims to study the relationship people have with built space. Employing space syntax on crusader castles brought new insights into the functioning of the fortress both in the social structure and behaviour of the inhabitants of the castles.